Design of hexagonal chalcogenide photonic crystal fiber with ultra-flattened dispersion in mid-infrared wavelength spectrum - S James Raja; Tony Jose; R Charlcedony; M Sam Paul; R Chakravarthi (Beni-Suef University Journal of Basic and Applied Sciences, 2022)
Abstract In the last few decades, silica-based photonic crystal fibers (PCFs) have been the subject of extensive research. Traditional silica-based PCFs, however, experience considerable propagation loss when used beyond 3000 nm. On the other hand, soft glasses, notably tellurite, fluoride, and chalcogenide glasses, offer exceptional optical transparency in the mid-IR wavelength region and are a desirable replacement for silica in MIR applications. A comprehensive investigation of chromatic dispersion properties in the hexagonal chalcogenide photonic crystal fibers is presented. The dependency of fiber dispersion on the structural parameters of photonic crystal fibers is thoroughly described in this study. Utilizing the interaction between material and geometrical dispersion, we were able to develop a well-defined framework for making specific predefined dispersion curves. In the mid-infrared wavelength spectrum, we are concerned with flattened, if not ultra-flattened, dispersion behaviors. In the wavelength range of 3500–6500 nm, the hexagonal chalcogenide microstructured fiber was engineered to achieve a typical dispersion profile flattened to within −3.41 to 9.5 ps/[nm–km] for the six-ring structure and −3.91 to 8.17 ps/[nm–km] for the four-ring structure. This proposed chalcogenide PCF can be used for soliton generation, gas sensing, biomedical imaging, supercontinuum generation, and long-distance high-speed communication applications in the mid-infrared wavelength range due to its nearly zero ultra-flattened dispersion characteristics.